Le rôle d’Internet et des technologies de l’information et de la communication dans le partage de connaissances sur l’adaptation des communautés côtières aux changements climatiques : retour sur l’expérience de création d’un contenu en ligne - Sebastian Weissenberger; Omer Chouinard (VertigO)
We describe the experience of creating online contents on climate change adaptation in coastal zones in a global perspective and the context in which the project took place. The objective of the project was information, communication, support to research-action projects in the field and networking. The use of internet and information and communication technologies (CIT) allows in theory to favour the dissemination of pilot projects and reach out to the numerous coastal communities in the world. However, the national and local contexts vary, especially regarding the capacity of communities to access online content. Furthermore, aiming the content at diverse audiences with different knowledge and interests requires to evaluate the legibility and usefulness of the content. In this context, it is very helpful to associate field actors in the process. Adaptation to climate change and variability in coastal zones is well suited for such a project, since environmental challenges and adaptation solutions are similar all over the world, and knowledge can therefore be used at a global scale.